Media Discourse Contestation on Indonesia's Energy Transition Policy: Network and Structural Analysis - Firdaus Cahyadi; Soeryo Adiwibowo; Edy Hartulistiyoso (Dinasti International Journal of Education Management And Social Science, 2025)
The Just Energy Transition Partnership (JETP) is a climate financing initiative launched by France, Germany, the United Kingdom, the United States, and the European Union. It was first introduced at the 26th Conference of the Parties (COP26) held in Glasgow, United Kingdom, in 2021. The JETP framework involves collaboration among various stakeholders, including governments, the private sector, and civil society organizations (CSOs), with the primary goal of supporting the implementation of the Paris Agreement. South Africa was the first country to receive JETP support, followed by Indonesia in 2022, during the G20 Summit in Bali. This study explores the contestation of energy transition policy discourses linked to Indonesia’s JETP initiative as represented in online media. To investigate this, the research analyzed 37 articles published by ten Indonesian online news outlets between January until December 31, 2022. The study employed Discourse Network Analysis (DNA) software to map patterns of discourse, and MICMAC (Matrix of Crossed Impact Multiplications Applied to a Classification) analysis to determine key discourse themes. The findings reveal that issues of transparency and public involvement emerge as central themes that significantly shape the direction of energy transition policy under the JETP initiative. This discourse of information transparency and public involvement is the gateway to expanding the space for energy transition policies. By expanding the space for policies, government dominance can be limited. These themes were consistently highlighted across media discourse, indicating their relevance both in academic inquiry and practical policymaking.